Potential Application of Ionic Liquids in Pharmaceutical Dosage Forms for Small Molecule Drug and Vaccine Delivery System - Mohammad Nasir Uddin; Debasish Basak; Robert Hopefl; Babak Minofar (Frontiers Media S.A., 2020)
Ionic liquids are salts in which the ions are poorly coordinated, which causes them to exist in liquid form below 100°C, or at room temperature. Therefore, these are also defined as room temperature ionic liquids (RTILs). In ionic liquids, at least one ion has a delocalized charge and one component is organic, which prevents the formation of a stable solid form of crystal lattice. Physical properties of ionic liquids, such as melting point, viscosity, and solubility of starting materials and other solvents, are impacted by the substituents on the organic component and by the counterions. Many ionic liquids have even been developed to address specific synthetic problems and that is the reason these are also termed as "designer solvents". Ionic liquids are considered as "green solvents" that exhibit several unique characteristics such as high ionic conductivity, high solvation power, thermal stability, low volatility, and recyclability. Although very useful with several advantages, ionic liquids have some limitations that include high cost and ease of recycling. Moreover, the toxicity and biodegradability of ionic liquids are not yet well understood. Nonetheless, ionic liquids can potentially be used in the field of pharmacy in drug design and formulation development. In drug or vaccine dosage formulation development, ionic liquids can be used as a solubility enhancer, permeability enhancer, stabilizer, targeted delivery inducer, stealth property provider or bioavailability enhancer. In this article we reviewed the physical properties of ionic liquids and potential application of ionic liquids in developing formulations for vaccines and small molecule drugs (A table has been added).